Teaching in a nutshell : navigating your teacher education program as a student teacher - Kosnik, Clare Madott; Beck, Clive (New York : c)
Each chapter deals with one of these priorities, using a common format. Chapters begin with the what and why of the priority in question, followed by a case study of a beginning teacher showing how he or she implements this priority. From there the authors outline some of the challenges of implementing the priority, and then describe principles and strategies for meeting these challenges.
Includes reference and index.
Keywords: Student teaching; Teachers -- Training of